2021
DOI: 10.1037/men0000346
|View full text |Cite
|
Sign up to set email alerts
|

Russian version of the Male Role Norms Inventory-Short Form: Structure, validity, and measurement invariance.

Abstract: The research presented here reports the process of adapting the Male Role Norms Inventory-Revised (MRNI-R) for use in Russian. The full (MRNI-R) and short form (Male Role Norms Inventory-Short Form; MRNI-SF) versions of the Inventory were tested in two studies. There were 1,016 participants in Study 1 and 1,038 participants in Study 2, which investigated second-order, seven-factor, and bifactor models. The analysis of construct validity indicated that the MRNI-R did not fit the data. Therefore, we developed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 27 publications
1
10
1
Order By: Relevance
“…It is worth noting that the results obtained in this study differ from the ones obtained in a recent previous study conducted on the Russian sample (Krivoshchekov et al, 2021). It evidenced that different elements of TMI, as measured by the MRNI-SF, can be viewed as a single construct.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that the results obtained in this study differ from the ones obtained in a recent previous study conducted on the Russian sample (Krivoshchekov et al, 2021). It evidenced that different elements of TMI, as measured by the MRNI-SF, can be viewed as a single construct.…”
Section: Discussioncontrasting
confidence: 99%
“…To measure TMI, we used the Russian version of the MRNI-SF (Krivoshchekov et al, 2021). The latter has previously demonstrated a reliable factor structure across gender and sexuality groups.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, some statements in the questionnaire may have a different meaning or not be relevant in a cultural group other than the one it was originally developed for and hence show poor cultural appropriateness (Swami & Barron, 2019). An alternative approach to the present study’s approach of focusing on keeping the translated version of the MRNI-SF as identical to the original version as possible is to modify certain statements in the questionnaire, for which cultural appropriateness cannot be assumed (Krivoshchekov et al, 2021). For example, the statement, “The President of the U.S. should always be a man,” may not be as relevant to the German-speaking population as to participants from the United States.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is also supported by studies that have indicated that straight and sexual minority individuals have different ideas about men and women. In particular, compared to sexual minority individuals, straight people endorse TMI more (Krivoshchekov et al, 2021;Wade &Donis, 2007). This difference is likely due to straight people expressing more negative attitudes than sexual minority individuals toward sexual minorities.…”
Section: Gender Ideology and Attitudes Toward Gay Peoplementioning
confidence: 93%